Designing School-Based Information Campaign to Prevent Sedentary Lifestyle: A Social Marketing Approach - Alifia Firliani; Suharyanti Suharyanti; Ani Fitriyah (Publikasi Indonesia, 2025)
Childhood and adolescent obesity is an increasingly critical public health challenge in Indonesia. Among its contributing factors, sedentary lifestyle is often overlooked compared to nutritional aspects. This study aims to evaluate the effectiveness of an informational campaign designed to promote active lifestyles as a strategy for obesity prevention among 4th and 5th-grade students in a suburban Jakarta school. The intervention was developed collaboratively with the school community, leveraging social marketing principles to ensure a theory-driven and effective approach. The half-day program included customized information delivery for children, outdoor games, and interactive sessions supported by teachers and staff. The evaluation employed both quantitative and qualitative methods through pre- and post-activity questionnaires, observations, and interviews. Results showed a significant increase in students’ knowledge about the benefits of physical activity, along with improved attitudes and intentions to adopt more active behaviours. Teachers also reported heightened awareness and integration of healthy habits into the school routine. The findings demonstrate that short-term informational interventions can yield meaningful outcomes in raising awareness and initiating behavioral change in children. This research provides a replicable early model for similar urban-fringe settings and highlights the importance of school-based initiatives in addressing childhood obesity.